Adaptation Of Building Information Modeling Among Quantity Surveyor Practitioners in Malaysia - Loo, Pei Yi (2013)
Building Information Modelling (BIM) has its root in the mid-1980s but only recently has it risen popularity BIM typically use three-dimensional, real-timer and also dynamic building modelling software. The model will stimulate design, operation, logistic, estimate and document. The process of BIM can show model in 3D drafting and 4D with time plans 5D with cost plans virtual modelling of building and 6D with life cycle management. Benefit of using BIM is better outcome through collaboration, design innovative in the earliest stage of project, deliver projects faster, and reduce wastage and so on. BIM has been used in many countries including Singapore. But the issue of IBM system is still new in the Malaysia building industry. Till now there is no study done on adaptability of BIM in Malaysia. So the research intends to study about BIM. The objectives of the study are identifying adaptability of BIM to QS practitioners in Malaysia practise and the readiness of QS practitioners in Malaysia of using BIM. For this study, the research had carried out in-dept. interview with Klang Valley area with QS practitioner. There are 4 out of 10 participants have been conducted the interview. The conclusion had drawn the study of adaption and readiness of QS practitioners for BIM. Furthermore, the research has identified some potential factors to educate the building industry players on the knowledge, problem of BIM implementation and assist the development of BIM for Malaysian construction industry.